Hras helps hippo heterodimerize to evade tumor suppression. (4th July 2018) - Araiza-Olivera, Daniela; Chernoff, Jonathan
ABSTRACT: Ras oncoproteins can promote or suppress cellular apoptosis, but the mechanisms underlying these varied responses remain incompletely understood. Ras is linked to the Hippo tumor suppressor pathway, a highly conserved signaling cassette that regulates organ size in animals ranging from flies to humans. The proximal members of this pathway, Mammalian Ste20-like kinases (Msts) −1 and −2, self-associate in homodimers and also form heterodimers with other proteins. Formation of such complexes is known to regulate Mst kinase activity and thus, the Hippo pathway. In a manuscript that recently appeared in Current Biology, we showed that activated Hras promotes the formation of Mst1/Mst2 heterodimers, that activation of Erk was required for this event, and that these heterodimers were much less active than Mst1/Mst1 or Mst2/Mst2 homodimers. Interestingly, the formation of such heterodimers was required to deactivate the Hippo pathway and to enable transformation by Hras. In this Commentary, we discuss the background for this study and surprising implications thereof.